If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 6 + -4p Solving -2 = 6 + -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. -2 + 4p = 6 + -4p + 4p Combine like terms: -4p + 4p = 0 -2 + 4p = 6 + 0 -2 + 4p = 6 Add '2' to each side of the equation. -2 + 2 + 4p = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4p = 6 + 2 4p = 6 + 2 Combine like terms: 6 + 2 = 8 4p = 8 Divide each side by '4'. p = 2 Simplifying p = 2
| x*2+4*x+3=4*x^2+2*x-1 | | 5x+4x-59=58 | | r^2-r+r-1=0 | | -7=w-22/3 | | 9k^2-30k+1=-24 | | 4(2m+5)=5(m+5)-7m | | 11x-86-x=94 | | 9k^2-30k=-25 | | m=3n+2p | | -3x-85+10x=34 | | -2x-5(x-3)=9 | | 2(h+1)=2 | | a^2x+ax+6a=a^2+12x+9 | | a^2x-4x-a=0 | | 2y-2y-7=6y+3-9y | | 5-n+7= | | 155/5 | | 0.2(2x-15)+0.6x=4.25 | | -i(4-8)= | | 0=4+5k-3k | | 5/155 | | 2x^3-39x^2+216x+3=f(x) | | a^2-4x-a=0 | | 15/7-1/14= | | -3x+4x-6k-7x= | | 5/2-1/4= | | 9k^2-30k+25=0 | | 8y+8=7y-5 | | 4(2y-4)=5y+42 | | 4x-y=3y+7x+8y | | 3x+4(-2+2x)=25 | | 2.7=0.7*x+0.9 |